Ceci n’est pas un dessin: notes on the production and sharing of fieldwork sketches - Ramos, M. J. (Cadernos de Arte e Antropologia, 2019)
Whereas the topic of how anthropologists link intimate written information gathered in the field with public production of knowledge in academic format – the so-called “writing culture” (an expression originated in Clifford and Marcus 1986) –, seems all but exhausted today, little attention has historically been given to the place and goals of sketching as part of that meandering process. The present contribution discusses the ontological and social conditions for the production and reception of knowledge-in-the-field sketches, on drawing as practice and as materiality, and on its bordering with writing.